The purest form of communicative power: A reinterpretation of the key to the legitimacy of norms in Habermas's model of democracy - Barreyro, María Emilia (2018)
The present paper offers an analysis of the Habermasian concept of communicative power by considering where communicative power arises from, establishing a criterion to distinguish the different forms it can adopt, and linking it to the anarchistic core of unleashed communicative freedomswhich Habermas admits his theory presupposes. My purpose is not only toclarify this key concept of his theory but also to illuminate, from a newangle, the accusation that Habermas's model of democracy is hostile todissensus and a threat to individuals that are not part of the mainstream of society. The thesis I will defend here holds that only a wide reading of theconcept of communicative power, which identifies the informal publicsphere as the source of the "purest form" of communicative power is consistent with the radical-democratic content of Habermas's theory and the power-dissolving character of public discussion. I also argue that, after clarifying those points, we will be able to see that Habermas's theory cannot be interpreted as either hostile or favourable to dissensus per seand that this criticism is mistaken due to its blindness to the normative dimension that communicative power involves